Prevalence of generalized joint hypermobility, musculoskeletal injuries, and chronic musculoskeletal pain among American university students - Peter R. Reuter; Kaylee R. Fichthorn (PeerJ, 2019)
The objective of this study was to investigate the prevalence of generalized joint hypermobility (GJH) in a university-aged population, whether young adults (aged 18–25 years) with GJH are prone to sustain more musculoskeletal injuries, and are more likely to suffer from chronic musculoskeletal pain. The study used an interactive survey to gather data; GJH was assessed using a cut-off Beighton score of ≥5 in accordance with the 2017 International Classification of EDS criteria. The analyzed sample consisted of 482 female and 172 male participants from Florida Gulf Coast University (USA). The prevalence of GJH in a university-aged population can be estimated at 12.5%. Women did not have higher rates of GJH than men. However, female participants showed significantly higher rates of hypermobility of the spine as well as the right knee and elbow joints. The Beighton scores did not differ by ethnicity/race. Female participants had a lower rate of self-reported injuries than male participants, although this difference was not significant. There was no difference in the proportion of all participants classified within different categories (0; 1–4; 5–9) of Beighton scores and whether or not they reported having been injured. Male and female participants reported chronic pain of joints and neck or back at the same rates across the Beighton score categories. Female participants, however, reported higher pain intensity for chronic neck and back pain. This study increases knowledge about a correlation between GJH, musculoskeletal injuries, and chronic pain of joints, neck, and back in a university-aged population.